Analisis Media Pembelajaran Pengenalan Huruf dan Angka pada Tingkat Sekolah Dasar Menggunakan Adobe Flash Professional CS6 - Nasution, Muhammad Bobbi Kurniawan; Ritonga, Theresia Rosalina; Kurniawan, Ridho; Ritonga, Sangkot Idris; Pohan, Muhammad Munawir (LPPPI Publishing, 2024)
Learning at the primary school level is an important stage for instilling strong basic concepts for students, especially in the introduction of letters and numbers. The use of appropriate learning media can improve student understanding. Adobe Flash Professional CS6 is one of the applications that can be used as interactive learning media for letter and number recognition. This study aims to analyze the use of Adobe Flash Professional CS6 in the introduction of letters and numbers in elementary schools. The method used is qualitative with a phenomenological study design, involving interviews, observation, and documentation. The research was conducted at a public elementary school in Labuhanbatu Regency, North Sumatra, with informants being the principal, school operator, and several classroom teachers. The results show that Flash-based learning media can visualize abstract concepts to be more concrete and interesting through animation and interactive features, thus helping students understand the material better and increasing their learning motivation. However, the use of digital-based learning media requires parental assistance to supervise children's use of technology. Training and capacity building of teachers in using information technology is also very important.